Antibakteri Fraksi n-Heksana Kulit Hylocereus polyrhizus Terhadap Staphylococcus epidermidis dan Propionibacterium acnes - Wahdaningsih, Sri; Untari, Eka Kartika; Fauziah, Yunita (UI Scholars Hub, 2014)
Acne can be caused by Staphylococcus epidermidis and Propionibacterium acnes. By using antibiotic for the acne theraphy in a long term period can cause resistance, organ detriment and imunohypersensitivity. Red dragon fruit’s peel (Hylocereus polyrhizus) is one of natural materials which can be used for alternative antibacterial. This study aims to determine the antibacterial activity of n-Hexane fraction of red dragon fruit’s peel against S. epidermidis dan P. acnes by the method of disc diffusion Kirby-Bauer. Red dragon fruit’s peel powder macerated within chloroform, and macerate then fractionated with n-Hexane. Phytochemical screening result red dragon fruit’s peel contains terpenoid and alkaloid. Clindamycin 4µg/disk were used for positive control while DMSO 10% were used for negative control. Data analyzed by using R-Commander program 3.0.3 version.This research show that n-Hexane fraction of red dragon fruit’s peel have antibacterial activity against P. acnes where the averagezone of inhibition obtained from the concentrations from 20; 40; and 80 mg/mL in a row were 9 mm; 10,25 mm; and 10,5 mm. In while, for S epidermidis n-hexane fraction of red dragon fruit’s peel didn’t have antibacterial activity.